PENGARUH KARAKTERISTIK TUJUAN ANGGARAN DAN GROUP COHESIVENESS TERHADAP KINERJA MANAJERIAL - Mutmainah, Mutmainah; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to find out the influence of characteristic of budget objectives and group cohesiveness to the managerial performance at the work unit of Local Apparatus in Surabaya. The population is the employee who has the involvement authority in the process of budget planning in the work unit of Local Apparatus in Surabaya with 76 people have been selected as samples. The variables in this research consist of two independent variables which are characteristic of budget objectives and group Cohesiveness and the dependent variable is the managerial performance. The analysis technique has been done by using multiple linear regressions with the rate of error tolerance are 5%. The result of the analysis shows that: characteristic of budget objectives has positive influence to the managerial performance, and Group Cohesiveness has positive influence to the managerial performance. It means that when the characteristic of the budget objectives and group cohesiveness is getting better, the managerial performance increases and vice versa.Keywords : Characteristic of Budget Objectives, Group Cohesiveness, Managerial Performance.